Rural and Urban Disparities of Scheduled Caste Population: A Study with Special Reference to Viluppuram District, Tamil Nadu - Dr. A. RANJITHKUMAR (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The scheduled caste population is being deprived segment of the population. It is necessary to see its progress in terms of demographic and socio-economic conditions to improve it with the help of existing and innovative programs available with the government and the voluntary organizations so that social and economic equality efforts could be made possible. The percentage of scheduled caste population and the other demographic characteristics such as sex ratio, literacy rate, and work participation rate of Tamil Nadu seem to be desirably high as compared to the national averages of the same. It is found that among 32 districts of Tamil Nadu, Thiruvalluvar district tops with 34 % of scheduled caste population, Tirunelveli tops in sex ratio in total and rural areas, Kanniyakumari tops in literacy rate in total, rural, urban among both males and females, Tiruppur tops in work participation rate both rural and urban areas and more or less among both males and females. Karur district has more male-female differences and Coimbatore district has more urban-rural differences in literacy rate. Chennai district accounts for more male-female differences and Kanniyakumari accounts for the more urban-rural difference in the work participation rate. It may be suggested that the District, which has more proportion of scheduled caste population with low sex ratio both in total and child populations and high gender and residential differences in literacy rate and works participation rate may be more concentrated with suitable awareness and reformative social welfare measures.